Exploring Legume-Rhizobia Symbiotic Models for Waterlogging Tolerance - Pucciariello, Chiara; Boscari, Alexandre; Tagliani, Andrea; Brouquisse, Renaud; Perata, Pierdomenico (Frontiers in Plant Science, 2019)
Unexpected and increasingly frequent extreme precipitation events result in soil flooding or waterlogging. Legumes have the capacity to establish a symbiotic relationship with endosymbiotic atmospheric dinitrogen-fixing rhizobia, thus contributing to natural nitrogen soil enrichment and reducing the need for chemical fertilization. The impact of waterlogging on nitrogen fixation and legume productivity needs to be considered for crop improvement. This review focuses on the legumes-rhizobia symbiotic models. We aim to summarize the mechanisms underlying symbiosis establishment, nodule development and functioning under waterlogging. The mechanisms of oxygen sensing of the host plant and symbiotic partner are considered in view of recent scientific advances.